2012
DOI: 10.1523/jneurosci.6022-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Olfactory Perception by Visual Cortex Stimulation

Abstract: When attempting to identify an object based on smell alone, people often visualize the perceived source of the odorant. This close association between olfactory and visual functions is supported by neuroimaging studies demonstrating activation of visual cortex during performance of purely olfactory tasks. Such activation might simply reflect the correlation between olfactory percepts and the corresponding visual images, or it might reflect a causal contribution of visual processing to olfactory perception. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Moreover, a decrease in grey matter volume of the fusiform gyrus, the middle temporal gyrus, and the middle occipital gyrus was demonstrated in previous voxel‐based morphometry studies in anosmics compared to healthy controls (Bitter et al, ; Peng et al, ), pointing to a possible role of these areas in olfactory processing. It has been suggested that during attempted identification of a smell, people might visualize the potential source of the odor (Jadauji et al, ). Thus, one might speculate whether patients scoring lower on the olfactory test in our study recruited the occipital network for visualization of the odor source less than patients achieving higher scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a decrease in grey matter volume of the fusiform gyrus, the middle temporal gyrus, and the middle occipital gyrus was demonstrated in previous voxel‐based morphometry studies in anosmics compared to healthy controls (Bitter et al, ; Peng et al, ), pointing to a possible role of these areas in olfactory processing. It has been suggested that during attempted identification of a smell, people might visualize the potential source of the odor (Jadauji et al, ). Thus, one might speculate whether patients scoring lower on the olfactory test in our study recruited the occipital network for visualization of the odor source less than patients achieving higher scores.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous evidence that patients with olfactory deficits show a reduced olfactory imagery capacity (Flohr et al, ; Kollndorfer et al, ). Furthermore, in a repetitive transcranial magnetic stimulation investigation, stimulation of the visual cortex led to improved odor discrimination performance as compared to sham stimulation, thus even pointing to a potential direct contribution of visual cortex to olfactory processing (Jadauji et al, ). The interconnection of the visual and olfactory system was also underlined by a recent study on olfactory‐visual conditioning (Hummel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Zellner and Whitten (1999) reported that while semantically congruent colors can enhance the intensity of a perceived odor (green for mint odor, red for strawberry odor), the effect was mainly due to the intensity of the color, while hue had little effect: The presence or absence of color in the concurrently presented solution seems to be an important factor (see also Zellner, Bartoli, & Eckard, 1991;Zellner & Kautz, 1990; but see , in addition to whether it was red or green. Going one step farther, recent imagery studies have suggested that vision contributes more generally to olfactory processing, as the mere stimulation of the visual cortex improves performance at the discrimination of different odor qualities (Jadauji, Djordjevic, Lundström, & Pack, 2012). In Seo, Arshamian, et al's (2010) study, the presentation of pairs of visual shapes and odors that had been rated as corresponding crossmodally in a previous task increased both the pleasantness (or unpleasantness) and intensity of the odors.…”
Section: Underevidenced Behavioral Effectsmentioning
confidence: 96%
“…However, it is also possible that the gustatory system directly influences olfactory processing at “earlier” processing levels. Given that recent work has revealed multisensory influences on primary sensory cortices (Ghazanfar et al, 2005; Lakatos et al, 2007; Iurilli et al, 2012)—including olfactory cortex (Gottfried and Dolan, 2003; Wesson and Wilson, 2010; Jadauji et al, 2012)—it is reasonable to ask whether the influence of taste on the olfactory system extends to primary cortical regions as well.…”
Section: Introductionmentioning
confidence: 99%